Is instant porridge with a high calcium content based on Moringa oleifera as an alternative baby food to prevent stunting in Indonesia? - Septa Katmawanti; Supriyadi Supriyadi; Fariha Mariroh (SAGE Publishing, 2021)
Background: According to WHO, stunting is a state of height-for-age index below minus two standard deviation. However, the condition could be prevented by giving suitable complementary food to babies and toddlers. Moringa leaves are rich in vitamins A, C, B6, as well as calcium, potassium, iron, as well as protein, and are therefore used as complementary foods for breast milk, in baby feeding. Design and Methods: Instant porridge was developed using three formulas. Each formula comprised Moringa leaf flour (5, 6 and 7 grams each) combined with 30 grams of oatmeal powder, 40 grams of powdered formula, 10grams of refined sugar, and 5 grams of banana flour. Results: Based on the organoleptic test, Formula 3 (created with 5 grams of Moringa leaf flour) was discovered to be the best. The organoleptic evaluation panel consisted of 3 trained and 30 untrained participants, while the statistical results showed the parameters of colour, texture, and taste, have no significant effect on panellists' acceptance. Conclusions: The flavour parameter has a significant effect on panellists' acceptance, with a p-value <0.05.